2017
DOI: 10.4103/jcrt.jcrt_1414_16
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric analysis of cardiac dose with or without active breath coordinator moderate deep inspiratory breath hold in left sided breast cancer radiotherapy

Abstract: We report that the use of ABC mDIBH technique resulted in a significant reduction in cardiac dose and hence can be considered as a promising tool for cardiac sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Many studies [32][33][34] have shown that deep inspiration breath hold (DIBH) can signi cantly reduce the radiation dose to the heart and lungs for breast cancer radiotherapy. However, the technique requires patients to hold their breath for a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [32][33][34] have shown that deep inspiration breath hold (DIBH) can signi cantly reduce the radiation dose to the heart and lungs for breast cancer radiotherapy. However, the technique requires patients to hold their breath for a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Uncommon but severe consequences are cardiac damage and lung dysfunction. 57 Concerning late shoulder complications, RT can be associated with numbness or weakness of the ipsilateral arm. 4 In the same way, surgery is responsible for reduction of range of motion, lymphedema, and neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, management of leukemic infiltration of both breasts by T-ALL by use of BART has not been previously addressed in the literature. BART has been the primary mode of radiotherapeutic management of breast cancer in our department given the reported dosimetric benefits and significantly improved normal tissue sparing with incorporation of breath holding at moderate deep inspiration during treatment simulation and delivery[8,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, mDIBH with the ABC system was developed for management of respiratory motion for thoracoabdominal tumors and has been used for this purpose in both conventionally fractionated radiotherapy regimens and Stereotactic Body Radiation Therapy applications[8,17-21]. In addition to respiratory motion management, an additional benefit of mDIBH with the ABC system for breast cancer includes minimizing exposure of the heart particularly for left-sided breast cancer patients along with improved sparing of other critical organs, which has been supported in previous studies[8,17,18].…”
Section: Discussionmentioning
confidence: 99%